A double-reinforced dust suppression material for suppressing dust from coal piles and a preparation method thereof

By preparing a dual-strengthening dust suppression material composed of polyvinyl alcohol, acetic acid, dilutorial, etc., the problem that existing water spraying methods are difficult to effectively suppress coal dust, and an efficient and economical coal dust suppression effect is achieved.

CN118562448BActive Publication Date: 2025-04-18SHANDONG UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410550507.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-06
Publication Date
2025-04-18
Estimated Expiration
2044-05-06

AI Technical Summary

Technical Problem

Among the existing coal mine dust suppression technology, the water spraying method is difficult to effectively suppress coal dust due to the hydrophobic nature of the coal, and it is time-consuming and labor-consuming, and the dust suppression efficiency is low.

Method used

A double-strength dust suppression material is used, which consists of polyvinyl alcohol, acetic acid, glutaraldehyde, catalyst, wetting agent and water retention agent. The dust suppression agent with good film-forming and viscosity characteristics is formed through esterification and acetal reaction.

Benefits of technology

The dust suppression material can effectively adsorb and capture coal dust particles, form a dense protective film, prevent the secondary flying of coal dust, improve dust suppression efficiency, and have good water retention and economicality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118562448B_ABST
    Figure CN118562448B_ABST
Patent Text Reader

Abstract

The invention discloses a double-reinforced dust suppression material for suppressing dust from coal piles and a preparation method thereof, and relates to the technical field of dust suppression in coal mines. The preparation process of the double-reinforced dust suppression material is as follows: polyvinyl alcohol and distilled water are added to a three-necked flask, and stirred in a water bath to dissolve; then glacial acetic acid and concentrated sulfuric acid are added, and magnetic stirring is performed to obtain a mixed solution I; the temperature is increased, and then glutaraldehyde is added, and magnetic stirring is performed to obtain a mixed solution II; the temperature is reduced to room temperature in a water bath, and the solution is placed in ice water, and then sodium hydroxide is slowly added to adjust the solution to neutrality to obtain a neutral mixed solution III; finally, fatty alcohol polyoxyethylene ether sodium sulfate and glycerol are added, and magnetic stirring is performed to dissolve to obtain the double-reinforced dust suppression material. The beneficial effects of the invention are that the selected raw materials are easy to obtain, the preparation process is simple, the cost is low, and it is easier to industrialize production; the double-reinforced dust suppression material prepared by the method has multiple excellent properties such as dust suppression, film forming, wettability, water retention, adhesion, economy, and environmental protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal mine dust suppression, and in particular to a double-reinforced dust suppression material for suppressing dust from a coal pile and a preparation method thereof. Background Art

[0002] Coal resources, as the primary energy source with the largest share of my country's energy consumption, will continue to dominate for a long time. Therefore, effective prevention and control of coal dust is of great significance to the safe production of coal mines and the occupational health and safety of underground workers.

[0003] At present, the main dust suppression methods in coal mines include ventilation, spraying dust suppressants, water injection and other methods. At present, coal mines often take measures such as ventilation and spraying to suppress dust, among which spray technology accounts for more than 95%. However, due to the hydrophobicity of coal, coal dust is difficult to be wetted, and it has no dust suppression effect after the water evaporates. This not only wastes water resources, but also consumes time and effort, so the dust suppression efficiency is low. Compared with traditional water spray dust suppression, chemical dust suppressants can wet, bond and condense coal dust, which can effectively suppress dust flying.

[0004] Therefore, preparing a dust suppression material that has the functions of water retention, wetting, dust capture, water saving, and can form a hard shell to suppress dust flying is of great significance and practical value for the safe, efficient and green production of coal mines. Summary of the invention

[0005] In order to solve the above technical problems, the present invention discloses a double reinforced dust suppression material for suppressing dust from coal piles and a preparation method thereof. The prepared double reinforced dust suppression material has good dust suppression and wettability, can effectively adsorb coal dust particles, and combined with its own good viscosity, can better capture fine coal dust in the air and eventually settle to form a film, effectively preventing the secondary flying of coal dust.

[0006] To achieve the above object, the present invention adopts the following technical solution: a double-reinforced dust suppression material for suppressing dust from coal piles,

[0007] The raw materials are measured by weight and include:

[0008] 3-5 parts of polyvinyl alcohol;

[0009] 3-5 parts of acetic acid;

[0010] 2-3 parts of dilute glutaraldehyde;

[0011] 1~2 parts of catalyst;

[0012] 3~4 parts of wetting agent;

[0013] 2~4 parts of water retaining agent;

[0014] The balance is distilled water.

[0015] Furthermore, the catalyst is concentrated sulfuric acid; the wetting agent is fatty alcohol polyoxyethylene ether sodium sulfate; and the water retaining agent is glycerol.

[0016] Furthermore, the mass fraction of the selected dilute glutaraldehyde is 5%.

[0017] Furthermore, the raw materials are calculated according to a weight ratio of polyvinyl alcohol: acetic acid: dilute glutaraldehyde: concentrated sulfuric acid: sodium fatty alcohol polyoxyethylene ether sulfate: glycerol = 5:5:3:1:4:3.

[0018] Furthermore, the quality of each raw material is:

[0019] Polyvinyl alcohol 1g

[0020] Acetic acid 1g

[0021] Dilute glutaraldehyde 0.6g

[0022] Concentrated sulfuric acid 0.2g

[0023] Fatty alcohol polyoxyethylene ether sodium sulfate 0.8g

[0024] Glycerin 0.6g

[0025] 200ml of distilled water.

[0026] The present invention also discloses a method for preparing the above-mentioned double-reinforced dust suppression material for suppressing dust from coal piles, which specifically comprises the following steps:

[0027] S1: Add 1 g of polyvinyl alcohol and 200 ml of distilled water to a 250 ml three-necked flask equipped with a stirrer, condenser, liquid seal and thermometer, and stir and dissolve in a 90 °C water bath for 2 h;

[0028] S2: Add 1 g of glacial acetic acid and 0.2 g of concentrated sulfuric acid into a three-necked flask, and then place the three-necked flask in a 70°C magnetic stirring water bath for 6 h to obtain a mixed solution I;

[0029] S3: The water bath was heated to 80°C, and then 0.6 g of glutaraldehyde was added to the mixed solution I, and magnetic stirring was performed for 2 h to obtain a mixed solution II;

[0030] S4: Cool the three-necked flask to room temperature in a water bath and place it in ice water, slowly add a certain amount of sodium hydroxide to adjust the pH of the solution to neutral, and obtain a neutral mixed solution III;

[0031] S5: Then, 0.8 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol were added to the neutral mixed solution III, and the mixture was placed in a magnetic stirring water bath at 35° C. and magnetically stirred for 30 minutes to dissolve, thereby obtaining the dual-reinforced dust suppression material.

[0032] In the present invention, the raw materials selected have the following characteristics:

[0033] Polyvinyl alcohol has good film-forming properties, adhesion, water solubility and biocompatibility, high safety, biodegradability, good mechanical properties and excellent hydrophilic properties. Because it contains many hydroxyl groups in its structure, the water resistance of the film after film formation is poor. After esterification modification, its water resistance and biodegradability can be improved to a certain extent.

[0034] Acetic acid is an organic monobasic acid whose aqueous solution is weakly acidic. The material is readily available and economical. Because it contains carboxyl groups in its structure, it often exists in the form of esters. Esterification reaction with alcohols can improve the stability of the product.

[0035] Glutaraldehyde is an organic compound, commonly used as a fungicide, food industry processing aid, disinfectant, tanning agent, wood preservative, medicine and polymer synthesis raw material, etc. Its own aldehyde group can react with hydroxyl groups to cross-link the hydroxyl groups and improve the stability of the modified product.

[0036] Sodium fatty alcohol polyoxyethylene ether sulfate has good surfactant wetting properties, and also has excellent water solubility, detergency, emulsification, foaming, resistance to hard water, mildness and antistatic advantages.

[0037] Glycerin has good water retention properties. It can attract the surrounding water molecules and lock them on the surface to form a moisturizing film to prevent the surface from drying out and maintain a certain degree of wetness. At the same time, glycerin can also improve the smoothness of the surface of the dust suppressant conjunctiva and prevent the surface hard shell from drying out and cracking, causing secondary dust.

[0038] In the preparation process of the present invention, polyvinyl alcohol and acetic acid undergo esterification reaction under the catalysis of a catalyst, and the esterification product undergoes acetalization reaction with glutaraldehyde, and the reaction equations are as follows:

[0039] .

[0040] The reaction process is as follows:

[0041] Reaction (1) indicates that acetic acid reacts with polyvinyl alcohol to undergo an esterification reaction under acidic conditions by heating, wherein the carboxyl group on the acetic acid molecule loses a hydrogen atom and an oxygen atom and reacts with a hydrogen atom on the hydroxyl group on the polyvinyl alcohol to generate free water. Since esterification reactions are usually reversible, that is, the reactants are not completely converted into products, some unreacted hydroxyl groups on the polyvinyl alcohol molecules will still exist in a free form, and this feature can be used to carry out reaction (2).

[0042] The carbonyl group on glutaraldehyde is a strong polar group, and the carbon group has a strong positive charge, so it is easy to react with nucleophilic reagents. The oxygen on the hydroxyl group in the alcohol has a lone pair of electrons and has a strong nucleophilicity. Oxygen attacks the carbonyl carbon with its lone pair of electrons to form an acetal bond. Glutaraldehyde reacts with the unreacted hydroxyl group on the esterification product under the catalysis of concentrated sulfuric acid to cross-link the two esterification product molecules to form a more stable network structure, while improving the water resistance of polyvinyl alcohol.

[0043] The beneficial effects of the present invention are:

[0044] (1) Acetic acid reacts with polyvinyl alcohol to undergo an esterification reaction, causing the hydroxyl group on the polyvinyl alcohol to remove a hydrogen atom, destroying the hydroxyl structure, reducing the hydroxyl ratio, and introducing ester groups on the polyvinyl alcohol molecule, thereby improving the water resistance of the polyvinyl alcohol film and improving its thermal stability, viscosity, water retention and other properties; glutaraldehyde further cross-links the unreacted hydroxyl groups on the esterification product to form a more stable network structure, further improving its own thermal stability and film strength.

[0045] (2) The modified product after the reaction is mixed with a wetting agent (sodium fatty alcohol polyoxyethylene ether sulfate) to reduce the surface tension of water, so that its molecules can be adsorbed on the surface of the coal dust and form a directional adsorption layer, thereby increasing the permeability of the dust suppressant, making the coal dust easier to be wetted, and at the same time being able to better capture fine coal dust and make it settle into clumps; adding a water-retaining agent (such as glycerol) can enhance the dust suppressant's anti-evaporation ability and prolong its action time, while improving the smoothness of the dust suppressant's film formation, effectively preventing cracking of the coal crust surface, further increasing the effective time of dust suppression, and reducing the possibility of secondary dust.

[0046] (3) Polyvinyl alcohol has good film-forming properties, degradability, and economy. Its molecules contain a large number of hydroxyl groups, which leads to its high water solubility, affecting the water resistance of its film-forming products. Esterification with acetic acid can reduce the proportion of hydroxyl groups on the molecule and improve water resistance. Acetalization of the esterified product with glutaraldehyde can further reduce the number of hydroxyl groups in the molecule and improve the stability after film formation. Compared with other monobasic or polybasic acids, acetic acid is safer and more operable. The use of dilute glutaraldehyde can reduce the intensity of the reaction to a certain extent, enhance the safety of the reaction process, and reduce the difficulty of production.

[0047] The raw materials selected in the present invention are easy to obtain, the preparation process is simple, the cost is low, and it is easier to industrialize production. The prepared double-reinforced dust suppression material has good dust suppression and wettability, can effectively absorb coal dust particles, and combined with its own good viscosity, can better capture fine coal dust in the air, and finally settle to form a film, effectively preventing the secondary flying of coal dust.

[0048] In summary, the double-reinforced dust suppression material prepared by the present invention has multiple excellent properties such as dust suppression, film-forming property, wettability, water retention, adhesion, economy, and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a schematic diagram of the process flow of Example 1 of the present invention. DETAILED DESCRIPTION

[0050] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention.

[0051] Example 1

[0052] A method for preparing a double-reinforced dust suppression material for suppressing dust from coal piles, the process flow is as follows Figure 1 As shown, the specific steps include:

[0053] (1) Add 0.6 g of polyvinyl alcohol and 200 ml of distilled water to a 250 ml three-necked flask equipped with a stirrer, condenser, liquid seal and thermometer, and stir and dissolve in a 90 °C water bath for 2 h;

[0054] (2) Add 0.8 g of glacial acetic acid and 0.2 g of concentrated sulfuric acid into a three-necked flask, place the three-necked flask in a 70°C magnetic stirring water bath and stir for 6 h to obtain a mixed solution I;

[0055] (3) The water bath was heated to 80°C, and then 0.4 g of glutaraldehyde (5% by mass) was added to the mixed solution I, and magnetic stirring was performed for 2 h to obtain a mixed solution II;

[0056] (4) Cool the three-necked flask to room temperature in a water bath and place it in ice water. Slowly add a certain amount of sodium hydroxide to adjust the pH of the solution to neutral, and obtain a neutral mixed solution III.

[0057] (5) Then, 0.8 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol were added to the neutral mixed solution III, and the mixture was placed in a magnetic stirring water bath at 35° C. and dissolved under magnetic stirring for 30 minutes to obtain a double-reinforced dust suppression material.

[0058] Example 2

[0059] A method for preparing a double-reinforced dust suppression material for suppressing dust from a coal pile comprises the following steps:

[0060] (1) Add 0.8 g of polyvinyl alcohol and 200 ml of distilled water to a 250 ml three-necked flask equipped with a stirrer, condenser, liquid seal and thermometer, and stir and dissolve in a 90 °C water bath for 2 h;

[0061] (2) Add 0.6 g of glacial acetic acid and 0.3 g of concentrated sulfuric acid into a three-necked flask, place the three-necked flask in a 70°C magnetic stirring water bath and stir for 6 h to obtain a mixed solution I;

[0062] (3) The water bath was heated to 80°C, and then 0.4 g of glutaraldehyde (5% by mass) was added to the mixed solution I, and magnetic stirring was performed for 2 h to obtain a mixed solution II;

[0063] (4) Cool the three-necked flask to room temperature in a water bath and place it in ice water. Slowly add a certain amount of sodium hydroxide to adjust the pH of the solution to neutral, and obtain a neutral mixed solution III.

[0064] (5) Then, 0.6 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.4 g of glycerol were added to the neutral mixed solution III, and the mixture was placed in a magnetic stirring water bath at 35° C. and dissolved under magnetic stirring for 30 minutes to obtain a double-reinforced dust suppression material.

[0065] Example 3

[0066] A method for preparing a double-reinforced dust suppression material for suppressing dust from a coal pile comprises the following steps:

[0067] (1) Add 1 g of polyvinyl alcohol and 200 ml of distilled water to a 250 ml three-necked flask equipped with a stirrer, condenser, liquid seal and thermometer, and stir and dissolve in a 90 °C water bath for 2 h;

[0068] (2) Add 0.6 g of glacial acetic acid and 0.2 g of concentrated sulfuric acid into a three-necked flask, place the three-necked flask in a 70°C magnetic stirring water bath and stir for 5 h to obtain a mixed solution I;

[0069] (3) The water bath was heated to 70°C, and then 0.6 g of glutaraldehyde (5% by mass) was added to the mixed solution I, and magnetic stirring was performed for 2 h to obtain a mixed solution II;

[0070] (4) Cool the three-necked flask to room temperature in a water bath and place it in ice water. Slowly add a certain amount of sodium hydroxide to adjust the pH of the solution to neutral, and obtain a neutral mixed solution III.

[0071] (5) Then, 0.8 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol were added to the neutral mixed solution III, and the mixture was placed in a magnetic stirring water bath at 40° C. and dissolved under magnetic stirring for 30 minutes to obtain a double-reinforced dust suppression material.

[0072] Example 4

[0073] A method for preparing a double-reinforced dust suppression material for suppressing dust from a coal pile comprises the following steps:

[0074] (1) Add 1 g of polyvinyl alcohol and 200 ml of distilled water to a 250 ml three-necked flask equipped with a stirrer, condenser, liquid seal and thermometer, and stir and dissolve in a 90 °C water bath for 2 h;

[0075] (2) Add 0.8 g of glacial acetic acid and 0.3 g of concentrated sulfuric acid into a three-necked flask, place the three-necked flask in a 70°C magnetic stirring water bath and stir for 6 h to obtain a mixed solution I;

[0076] (3) The water bath was heated to 70°C, and then 0.5 g of glutaraldehyde (5% by mass) was added to the mixed solution I, and magnetic stirring was performed for 3 h to obtain a mixed solution II;

[0077] (4) Cool the three-necked flask to room temperature in a water bath and place it in ice water. Slowly add a certain amount of sodium hydroxide to adjust the pH of the solution to neutral, and obtain a neutral mixed solution III.

[0078] (5) Then, 0.6 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol were added to the neutral mixed solution III, and the mixture was placed in a magnetic stirring water bath at 40° C. and magnetically stirred for 30 minutes to dissolve, thereby obtaining a double-reinforced dust suppression material.

[0079] Example 5

[0080] A method for preparing a double-reinforced dust suppression material for suppressing dust from a coal pile comprises the following steps:

[0081] (1) Add 1 g of polyvinyl alcohol and 200 ml of distilled water to a 250 ml three-necked flask equipped with a stirrer, condenser, liquid seal and thermometer, and stir and dissolve in a 90 °C water bath for 2 h;

[0082] (2) Add 1 g of glacial acetic acid and 0.1 g of concentrated sulfuric acid to a three-necked flask, place the three-necked flask in a 70°C magnetic stirring water bath and stir for 7 h to obtain a mixed solution I;

[0083] (3) The water bath was heated to 80°C, and then 0.4 g of glutaraldehyde (5% by mass) was added to the mixed solution I, and magnetic stirring was performed for 2 h to obtain a mixed solution II;

[0084] (4) Cool the three-necked flask to room temperature in a water bath and place it in ice water. Slowly add a certain amount of sodium hydroxide to adjust the pH of the solution to neutral, and obtain a neutral mixed solution III.

[0085] (5) Then, 0.8 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol were added to the neutral mixed solution III, and the mixture was placed in a magnetic stirring water bath at 30° C. and magnetically stirred for 30 minutes to dissolve, thereby obtaining a double-reinforced dust suppression material.

[0086] Comparative Example 1

[0087] Add 200 ml of distilled water to a beaker, then add 0.8 g of polyvinyl alcohol to the beaker, and place the beaker in a 90°C magnetic stirring water bath to dissolve for 2 hours. Subsequently, add 0.8 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol to the polyvinyl alcohol aqueous solution, and place it in a 30°C magnetic stirring water bath to dissolve for 30 minutes.

[0088] Comparative Example 2

[0089] Add 200 ml of distilled water, 0.8 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol to a beaker, and place in a 30°C magnetic stirring water bath and stir until dissolved.

[0090] The double-reinforced dust suppression materials prepared in Examples 1-5 and Comparative Examples 1-2 were tested for water retention, dust suppression performance, and crust hardness.

[0091] 1. Water retention test:

[0092] Specific process: Use a vacuum drying oven to test its water retention rate and explore the water retention of each material on coal dust. Weigh the initial mass of the sample m 1 Place the sample in a vacuum drying oven at 60°C and dry it. Record the sample mass every hour, recorded as m 2 The total drying time is 12 hours, and the cycle is repeated 10 times to obtain the water retention rate within 12 hours. The specific calculation formula is as follows:

[0093]

[0094] Where W is the water retention rate of the dust suppression material sample (%), m 1 is the initial mass of the coal sample just sprayed with dust suppression materials (g), m 2 is the mass of the coal sample after a period of time (g).

[0095] The water retention test results are shown in Table 1 below.

[0096] Table 1

[0097]

[0098] 2. Dust suppression performance test

[0099] Specific process: The sample was placed in a simulated experimental platform with a wind speed of 12m / s, and a handheld laser particle counter (9306-V2) was used to detect PM 2.5 and PM 10 The concentration is recorded as C 0 Then, a certain amount of dust suppression material is evenly sprayed on the coal powder. After 48 hours, the sample is placed in a simulation test platform at 12 m / s to detect the concentration of PM2.5 and PM10, and the concentration is recorded as C 1 .

[0100] The data were measured 3 times and the average value was taken. The specific calculation formula is as follows:

[0101]

[0102] Where S is the dust suppression rate (%), C 0 is the initial concentration of PM2.5 and PM10 (μg / m 3 ), C 1 PM after spraying various dust suppression materials and water 2.5 and PM 10 The concentration (μg / m 3 ).

[0103] 3. Crust hardness test

[0104] Specific process: Use an electronic balance to weigh 5g of coal powder and spread it flat on a culture dish, evenly weigh 10g of dust suppressant solution and spray it on the coal sample, put the sample into a constant temperature drying oven at 50℃ and dry it for 6h, and use a Shore hardness tester to record the hardness value of each sample.

[0105] The crust hardness test results are shown in Table 2 below.

[0106] Table 2

[0107]

[0108] When the double-reinforced dust suppression material solution prepared by the present invention is sprayed on an open-air coal pile, the excellent dust suppression and water retention properties, combined with its good film-forming properties, form a dense protective film on the surface of the coal pile to prevent the flying of coal dust.

[0109] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Changes, modifications, additions or substitutions made by technicians in this technical field within the essential scope of the present invention should also fall within the protection scope of the present invention.

Claims

1. A method for preparing a double-reinforced dust suppression material for suppressing dust from coal piles, characterized in that: The specific steps include: S1: Add 1 g of polyvinyl alcohol and 200 ml of distilled water to a 250 ml three-necked flask equipped with a stirrer, condenser, liquid seal and thermometer, and stir and dissolve in a 90 °C water bath for 2 h; S2: Add 1 g of glacial acetic acid and 0.2 g of concentrated sulfuric acid into a three-necked flask, and then place the three-necked flask in a 70°C magnetic stirring water bath for 6 h to obtain a mixed solution I; S3: The water bath was heated to 80°C, and then 0.6 g of glutaraldehyde was added to the mixed solution I, and magnetic stirring was performed for 2 h to obtain a mixed solution II; S4: Cool the three-necked flask to room temperature in a water bath and place it in ice water, slowly add a certain amount of sodium hydroxide to adjust the pH of the solution to neutral, and obtain a neutral mixed solution III; S5: Then, 0.8 g of sodium fatty alcohol polyoxyethylene ether sulfate and 0.6 g of glycerol were added to the neutral mixed solution III, and the mixture was placed in a magnetic stirring water bath at 35° C. and magnetically stirred for 30 minutes to dissolve, thereby obtaining the dual-reinforced dust suppression material.

2. The method for preparing a double-reinforced dust suppression material for suppressing dust from coal piles according to claim 1, characterized in that: The mass fraction of the glutaraldehyde selected is 5%.

Citation Information

Patent Citations

  • Preparation method of special dust suppressant for soil surface

    CN107746701A

  • Sustained-release dust suppression microcapsule, and preparation method and application thereof

    CN111848870A